An Orthodontic Plier with Protractor for Orthodontic Wire bending - Ibrahim Alshahrani; Ali Alhaizaey (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
An inventive orthodontic instrument intended to improve accuracy during orthodontic wire bending operations. With the use of a unique tool called the Orthodontic Plier with Protractor, orthodontists can now manipulate wire at precise angles due to its integrated protractor. This development offers a simplified approach to orthodontic treatment while addressing the drawbacks of conventional techniques. By providing real-time angle measurement, the integrated protractor promotes uniformity in wire adjustments and improves treatment results. The plier's ergonomic comfort is prioritized in its design, making it simple for orthodontic practitioners to use. The Orthodontic Plier with Protractor is a useful addition to orthodontic instruments that advances accuracy and efficiency in orthodontic wire bending procedures by fusing functionality with user-friendly characteristics. By using this cutting-edge tool, practitioners support the ideas of technology integration and evidence-based practice while also furthering the continual evolution of orthodontics.